(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Developing clinical thinking competencies among future physicians is one of the core objectives of modern medical education. The dynamic nature of medicine, combined with rapid scientific and technological advancements, requires medical students to develop the ability to analyze clinical data, reason diagnostically, and make evidence-based decisions. This study aims to improve the methodology of forming clinical thinking competencies among medical students through the integration of simulation-based learning, problem-based learning (PBL), and reflective practice. A mixed-methods research design was used to evaluate the effectiveness of a proposed pedagogical model that enhances clinical reasoning, diagnostic accuracy, and decision making skills.